Effects of English Songs on EFL Learners’ Speaking Production and Their Perceptions - Kitjaroonchai, Tantip (12th International Scholars Conference 2025, 2026)
Although English songs are recognized as beneficial in EFL instruction, research on their impact on learners’ speaking performance and perceptions remains limited. This study investigated the effects of integrating English songs into speaking lessons for 28 first-year EFL students at a private university in Thailand and explored students’ perceptions of using songs to improve speaking. Over fifteen weeks, participants received two weekly sessions incorporating contemporary songs. A one-group pretest-posttest design was used, with speaking tests (pretest, posttest, delayed posttest) analyzed via paired-sample t-tests and descriptive statistics. Results showed significant improvements in overall speaking performance from pretest to posttest (p < .001, d = 1.84) and sustained gains in the delayed posttest (p < .001, d = 1.98). Lexical density improved only in the delayed posttest (p < .05, d = 0.43), while accuracy and fluency increased significantly (errors per 100 words, p < .05, d = 0.49; error-free clauses, p < .05, d = –0.59; words per minute, p < .001, d = 1.09). Survey results indicated that students viewed song integration positively for enhancing speaking skills. These findings suggest that English songs are an effective pedagogical tool for developing EFL learners’ speaking performance. Limitations include the small sample size and lack of a control group, but the study offers practical implications for engaging speaking instruction in EFL contexts.